A Fatal Case of Legionella bozemanii Pneumonia in an Immunocompetent Patient - Atif Saleem Siddiqui (Case Reports in Pulmonology)
Legionella bozemanii pneumonia is a rare form of Legionnaires’ disease caused by the bacterium Legionella bozemanii. It is well known to cause pneumonia in immunocompromised patients and has rarely been reported in immunocompetent hosts. We describe a case of a 59-year-old immunocompetent female presented with pneumonia, acute respiratory failure, acute respiratory distress, and septic shock, who was treated with azithromycin, goal-directed resuscitation, and extracorporeal membrane oxygenation (ECMO) but did not survive. Clinicians should have high suspicion of rare legionella pathogens as causative agents for pneumonia.